Height and Weight of Preschool children of well-to-do Urban Families in Jakarta City - Sri Rochani Sudjarwo; Sunarwati Sularyo; Sudiyanto Sudiyanto; Aliamran Rasjid (Paediatrica Indonesiana, 1978)
From studies of the Indonesian children in good socio-economic condition a conclusion can be made, that they are all in a good nutritional status, so that this physical dimension can be used as indices of health of the Indonesian preschool children. But this so-called ethnic standard, using an â€optimumâ€ group, must be kept up-to-date and reviewed every 5 years or so (Janes, 1975), remembering the probable existence of a secular trend. It is still a task to do for establishing the most effective methods to bring about an all-round improvement in the health and nutritional status of the children as great as possible, and to enable the children to get more benefit from the education which is available.